Education Regarding Food Additives for Residents of RT 29 Kelurahan 15 Ulu, Jakabaring District, Palembang City, South Sumatra Province - Idealistuti, Idealistuti; Suyatno, Suyatno; Yani, Ade Vera; Fahmi, Inneke Abdillah; Hawa, Putri Siti (Altifani Journal: International Journal of Community Engagement, 2022)
Food Additives (BTP) According to the Regulation of the Minister of Health of the Republic of Indonesia Number. 33 of 2012 it is explained that BTP is an ingredient that is not usually used as food and is usually not a typical food ingredient, has or does not have nutritional value, which is intentionally added to food. The location for Community Service was held at RT.29 Kelurahan 15 Ulu, Jakabaring District, Palembang City, on September 2, 2021. The method used was counseling to participants about food additives. The implementation of the activity was attended by 15 participants, with enthusiasm and discussions and questions and answers during the extension. The results of this Community Service show that the service method in the form of counseling, and question and answer is very appropriate in providing motivation to the community to add insight into food additives.